Superplasticity in Gold Nanowires through the Operation of Multiple Slip Systems. (21st October 2018) - Cao, Guang; Wang, Jiangwei; Du, Kui; Wang, Xuelu; Li, Jixue; Zhang, Ze; Mao, Scott X.
Abstract: Dislocation activity in metallic nanowires often causes shear localization and premature necking, resulting in an early fracture. Here, in situ nanomechanical testing reveals a strong orientation‐dependent dislocation‐mediated superplastic deformation in gold (Au) nanowires, with more than 100% uniform elongation achieved before the fracture of [111]‐oriented nanowires. Such superplastic deformability of [111]‐oriented Au nanowires originates from the close coordination of homogeneously activated dislocation events on the three equivalent slip planes, which effectively eliminates the dislocation‐induced deformation localization in Au nanowires with other orientations. This work sheds new light on the dislocation plasticity in metallic nanostructures, and is of technological importance for designing metallic nanostructures and nanodevices with high reliability. Abstract : Gold (Au) nanowires show a strong orientation‐dependent dislocation‐mediated superplastic deformation, where the [111]‐oriented nanowires present more than 100% uniform elongation before fracture. Quantitative analysis shows that the superplastic deformability of [111]‐oriented Au nanowires originates from the close coordination of homogeneously activated dislocation events on three equivalent slip planes, which effectively eliminates the dislocation‐induced deformation localization.